Synthesis of eupomatilone-6 and assignment of its absolute configuration - Gurjar, Mukund K.; Karumudi, Bhargava; Ramana, C. V. (Journal of Organic Chemistry, 2005)
[GRAPHICS] The Zn-mediated Barbier reaction of the biarylaldehyde 8 with crotyl bromide followed by hydroboration and oxidation provided the gamma-butyrolactones 4 and 5. The stereoselective installation of methyl group at C-3 by using LiHMDS and MeI completed the synthesis of racemic eupomatilone-6 (2) and its diastereomer 3. The spectroscopic data of 2 was in fall agreement with reported spectra of natural product, thus confirming the revised relative configuration of eupomatilone-6. Similarly, an optically active (3R,4R,5S)-isomer of eupomatilone-6 (23) was prepared in which the aldol reaction with thiazolidinethione as a chiral auxiliary was employed as a key step. On the basis of the spectroscopic data and optical rotation values of 23, the absolute configuration of eupomatilone-6 was proposed.

Stereoselective synthesis of the polyketide chain of nagahamide A - Mohapatra, Debendra K.; Chaudhuri, Siddhartha Ray; Sahoo, Gokarneswar; Gurjar, Mukund K. (Tetrahedron-Asymmetry, 2006)
A carbohydrate based approach for the enantioselective synthesis of the polyketide acid unit present in nagahamide A has been reported. Reductive ring opening of a chiral cyclopropane ketone group to enantioselectively install the methyl and propyl groups, is a salient feature of this synthesis. (c) 2006 Elsevier Ltd. All rights reserved.

Synthesis of the spiro fused beta-lactone-gamma-lactam segment of oxazolomycin - Mohapatra, Debendra K.; Mondal, Dhananjoy; Gonnade, Rajesh G.; Chorghade, Mukund S.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
An effective synthetic strategy for construction of the novel spiro-bicyclic beta-lactone-gamma-lactam system present in oxazolomycin has been demonstrated. The 3,4-disubstituted pyrrolidine ring system was constructed via an Evans aldol reaction. The spiro-beta-lactone ring was elaborated from a gem-hydroxymethyl moiety that was successfully installed by an aldol followed by a crossed Cannizzaro reaction. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: crossed Cannizzaro reaction; Evans' aldol reaction; Garner's aldehyde; intramolecular Mitsunobu reaction; ruthenium tetroxide oxidation

Synthetic studies toward macrocidins: an RCM approach for the construction of the central cyclic core - Ramana, C. V.; Mondal, Mohabul A.; Puranik, Vedavati G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
The central macrocyclic core of the macrocidins was constructed using RCM as the key reaction. A preliminary investigation dealing with the key reactions, that is, the Dieckmann cyclization and the RCM, revealed that RCM of the beta-ketoamide is better than RCM of the corresponding acyltetramic acid. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: acyltetramic acid; Lacey-Dieckmann cyclization; macrocidins; Ring closing metathesis

Short and efficient synthetic strategy for the total syntheses of (S)-(+)- and (R)-(-)-Plakolide A - Mohapatra, Debendra K.; Pramanik, Chintnoy; Chorghade, Mukund S.; Gurjar, Mukund K. (European Journal of Organic Chemistry, 2007)
Concise and efficient total syntheses of anticancer agents (S)(+)-Plakolide A and (R)-(-)-Plakolide A were accomplished in eight steps and an overall yield of 39 % starting from geraniol. The key steps in our strategy are Sharpless asymmetric epoxidation, double elimination, and Stille coupling reactions.
Keywords: Cross-coupling; epoxidation; inhibitors; olefination

Syntheis of unusual tricyclic ring systems of biological interest - Mohapatra, Debendra K.; Maity, Pradip K.; Chorghade, Mukund S.; Gurjar, Mukund K. (Heterocycles, 2007)
We describe a new synthesis of tricyclic scaffolds that incorporate a fusion of triazole with 1,4-benzodiazepine utilizing intramolecular ``click'' chemistry.
Keywords: 1; 2; 3-Triazole; 4-benzodiazepine; Click chemistry; nitrogen rich polycyclic hetero-system; privileged structure

Synthesis and evaluation of 4/5-hydroxy-2,3-diaryl(substituted)-cyclopent-2-en-1-ones as cis-restricted analogues of combretastatin A-4 as novel anticancer agents - Gurjar, Mukund K.; Wakharkar, Radhika D.; Singh, Anu T.; Jaggi, Manu; Borate, Hanumant B.; Shinde, Popat D.; Verma, Ritu; Rajendran, Praveen; Dutt, Sarjana; Singh, Gurvinder; Sanna, Vinod K.; Singh, Manoj K.; et al. (Journal of Medicinal Chemistry, 2007)
A new series of 2,3-diaryl-4/5-hydroxy-cyclopent-2-en-1-one analogues replacing the cis double bond of combretastatin A-4 (CA-4) by 4/5-hydroxy cyclopentenone moieties was designed and synthesized. The analogues displayed potent cytotoxic activity (IC50 < 1 mu g/mL) against a panel of human cancer cell lines and endothelial cells. The most potent analogues 11 and 42 belonging to the 5-hydroxy cyclopentenone class were further evaluated for their mechanism of action. Both of the analogues led to cell cycle arrest at G2/M phase and induced apoptosis in endothelial cells. Antitubulin property of 42 was superior to 11 and comparable to CA-4. The compound 42 had better aqueous solubility, metabolic stability, and pharmacokinetic profile than CA-4 and also demonstrated significant tumor regression in the human colon xenograft model. Our data suggests that cis-restricted analogues of CA-4 are a new class of molecules that have the potential to be developed as novel agents for the treatment of cancer.

Synthesis of L-ido-configured six- and seven-membered carba-sugars - Ramana, C. V.; Chaudhuri, Siddhartha Ray; Gurjar, Mukund K. (Synthesis-Stuttgart, 2007)
Ring-closing olefin metathesis has been successfully applied to the modular construction of L-ido-configured six- and seven-membered carba-sugars.
Keywords: allylations; carbocycles; carbohydrates; Metathesis; Radical reactions

Synthesis of the C19-C34 segment of amphidinolide C - Mohapatra, Debendra K.; Rahaman, Hasibur; Chorghade, Mukund S.; Gurjar, Mukund K. (Synlett, 2007)
The synthesis of the C19-C34 segment of amphidinolide C is described. The key steps include the Mioskowski's Lewis acid catalyzed epoxide opening with the alcohol, ring-closing metathesis, Wittig reaction, and Nozaki-Hiyama-Kishi coupling reaction.
Keywords: amphidinolide C; Cytotoxic; Nozaki-Hiyama-Kishi coupling; Ring-closing metathesis; Wittig reaction

Short total synthesis of (+)-cryptocarya diacetate - Gurjar, Mukund K.; Raghupathi, Neelarapu; Chorghade, Mukund S. (Heterocycles, 2009)
A short synthesis of (+)-cryptocarya diacetate was achieved by employing three component linchpin coupling, diastereoselective reduction of beta-hydroxyketone, and Z-selective HWE reaction as key transformations.
Keywords: Brook Rearrangement; cryptocarya diacetate; Diastereoselective Reduction; Horner-Wadswarth-Emmons Reaction; Linchpin coupling

Studies toward the total synthesis of carba analogue of motif C OF M. TB cell wall AG complex - Gurjar, Mukund K.; Reddy, Challa Nageswar; Kalkote, Uttam R.; Chorghade, Mukund S. (Heterocycles, 2009)
Herein we describe the synthesis of the carba analogue of motif C of arabinogalactan complex present in M tuberculosis cell wall. Pd(0) catalyzed allylic alkylation and Fraser-Reid's glycosidation are the two key reactions that were employed for the synthesis of central glycosyl accepter unit and the glycosylation respectively.
Keywords: Allylic Alkylation; desymmetrization; Fraser-Reid's Glycosidation; M. Tb Ag Complex; Mycobacterium tuberculosis

Syntheis of new chiral 5,6,7,8-tetrahydrotetrazolo[1,5-a]pyrazines from alpha-amino acid derivatives following ``click'' chemistry - Mohapatra, Debendra K.; Maity, Pradip K.; Ghorpade, Ravindra V.; Gurjar, Mukund K. (Heterocycles, 2009)
An efficient and practical synthesis of new chiral fused tetrazoles have been synthesized following [3+2] cycloaddition reaction starting from alpha-amino acid derivatives.
Keywords: Amino acid; Click chemistry; Hypertension; Nitrogen Rich System; Tetrazole

Stereoselective formal total synthesis of novel antibiotic (-)-centrolobine - Mohapatra, Debendra K.; Pal, Rita; Rahaman, Hasibur; Gurjar, Mukund K. (Heterocycles, 2010)
A concise and stereoselective formal total synthesis of (-)-centrolobine is achieved utilizing Mioskowski's Lewis acid mediated epoxide opening followed by ring-closing metathesis as the key reaction.
Keywords: antibiotic; Centrolobine; Keck allylation; Ring-closing metathesis; Sharpless asymmetric epoxidation

Synthetic studies of superstolide A: a carbohydrate based synthesis of the C21-C26 segment - Pal, Rita; Rahaman, Hasibur; Mohapatra, Debendra K.; Gurjar, Mukund K. (Letters in Organic Chemistry, 2010)
The synthesis of C21-C26 fragment of superstolide A, starting from D-glucose diacetonide, involving regioselective ring opening of epoxide by Grignard reagent and regioselective stereospecefic hydroboration oxidation has been described.
Keywords: Chiral pool; Potent cytotoxic; Regioselective epoxide opening; Stereoselective hydroboration-oxidation; Superstolide A

Synthesis of (+/-)-thia-calanolide A, its resolution and in vitro biological evaluation - Chopade, Anil U.; Chopade, Manojkumar U.; Chanda, Bhanu M.; Sawaikar, Dilip D.; Sonawane, Kiran B.; Gurjar, Mukund K. (Arabian Journal of Chemistry, 2016)
A synthesis of (+/-)-thia-calanolide A 3 has been successfully accomplished starting from 3,5-dimethoxythiophenol 4, in six steps in an overall yield of 4.5%. The key reaction involved Friedel-Crafts tigloylation of 5,7-dihydroxy-4-n-propyl thiocoumarin 6 employing an appropriate solvent of CS2-PhNO2 in a ratio of 7:3. In its biological evaluation for anti-HIV activity, (+/-)-thia-calanolide A 3 demonstrated comparatively less activity with calanolide A and its synthetic analogue aza-calanolide. Further, (+/-)-3 has been resolved by chiral HPLC to (+) and (-)-3. (C) 2012 Production and hosting by Elsevier B.V. on behalf of King Saud University.